2022
DOI: 10.3390/pharmaceutics14071431
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Polymer Blends in the Treatment of Ocular Diseases

Abstract: The eye is an organ with limited drug access due to its anatomical and physiological barriers, and the usual forms of ocular administration are limited in terms of drug penetration, residence time, and bioavailability, as well as low patient compliance. Hence, therapeutic innovations in new drug delivery systems (DDS) have been widely explored since they show numerous advantages over conventional methods, besides delivering the content to the eye without interfering with its normal functioning. Polymers are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 178 publications
0
7
0
Order By: Relevance
“…The poor mechanical performance observed in the PET-PBS formulation with PBS contents of 2.5, 5, 7.5, 10, and 15 wt.% indicates that PBS is immiscible with PET, even at low contents [30]. The theoretically calculated solubility using Small's method could indicate that the affinity or partial miscibility between PET and PBS could be obtained only at even lower PBS contents than in this study.…”
Section: Mechanical Characterizationmentioning
confidence: 51%
“…The poor mechanical performance observed in the PET-PBS formulation with PBS contents of 2.5, 5, 7.5, 10, and 15 wt.% indicates that PBS is immiscible with PET, even at low contents [30]. The theoretically calculated solubility using Small's method could indicate that the affinity or partial miscibility between PET and PBS could be obtained only at even lower PBS contents than in this study.…”
Section: Mechanical Characterizationmentioning
confidence: 51%
“…In addition, PVA-CS was investigated for its potential use in the treatment of ocular surface disorders such as dry eye syndrome. It was shown to improve tear film integrity and minimize ocular surface damage [ 97 , 105 ]. Therefore, PVA-CS seems to be a good system for drug delivery in ophthalmology and for treating ocular surface diseases.…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%
“…Even though Mesoporous Silica Nanoparticles (MSNs) have a low degradability due to their pure silica framework, current research has shown that MSNs can be changed to reach a biodegradation that is adequate for clinical applications. Researchers Fan et al ( 2021) utilised biodegradable hollow mesoporous organosilica (HOS) nanocapsules to distribute NO in a stimulusresponsive way for the purpose of increased penetration and bioavailability [53]. In spite of the fact that it had an effect on reducing IOP, it had been discovered in the past that extended usage of NO-MSNs led to an increase in IOP elevation after the first decrease [54].…”
Section: Preclinical Studiesmentioning
confidence: 99%